PENINGKATAN KINERJA PLTB MELALUI KENDALI FREKUENSI FUZZY LOGIC - Kiswantono, Agus; Hermanto, Yuli (Jurnal Informatika dan Teknik Elektro Terapan, 2024)
This research explores the use of a Governor as a frequency control mechanism in a power generation system by implementing two control methods: Proportional-Integral (PI) Controller and Fuzzy Logic Controller (FLC). The objective of the study is to evaluate the dynamic frequency response of the system and compare the performance of both control methods against the permissible standard, which is within the range of 50±2% (49 Hz to 51 Hz). Through simulations of a power generation system, parameters were adjusted to achieve the target frequency, and both control methods were evaluated. The results indicate that both methods can maintain the frequency within the desired range. However, Fuzzy Logic Controller on the Governor produces a superior dynamic frequency response with a lower steady-state error percentage. The implementation of Fuzzy Logic Controller also demonstrates a faster time to reach steady state compared to the PI Controller method. This superiority suggests that FLC provides more adaptive and responsive control to load fluctuations, enhancing the efficiency and stability of the power generation system.This research provides deeper insights into optimizing frequency control on Governors, particularly through the use of Fuzzy Logic Controller. Consequently, the development of this technology has the potential to improve the performance and reliability of power generation systems, supporting the transition towards a more efficient and sustainable electric grid.